Environmental factors influencing the settlement of Diplodus spp. juveniles in temperate marine rocky shores - Coelho, Pedro Miguel Janeiro Duarte (2019)
Long-term monitoring programs can reveal trends emerging from yearly fluctuations that are difficult to evaluate in short-term studies. A 10-year study focused on four Diplodus species whose juveniles regularly use coastal reefs as nursery areas was performed in a recently classified Marine Protected Area (MPA). Differences in microhabitat use and a photographic guide for juvenile identification is provided. Environmental variables such as sea surface temperatures, air temperature, wave period and wind speed explain 53,4% of the interannual variation in juvenile abundances. A decreasing trend observed in juveniles from 2012-2017 was mirrored by adult fish landings in adjacent fishing ports, highlighting the importance of monitoring programs within MPA's for the management of species with commercial interest. Furthermore, the biogeographic transition between warm and cold temperate habitats along the Portuguese coast, enables the identification of sudden settlement pulses of warm water species in years with milder temperatures; Resumo: Os programas de monitorização a longo prazo são importantes por permitirem destrinçar pequenas variações interanuais, impossíveis de verificar em estudos de curta duração. Este estudo de 10 anos realizou-se numa zona marinha rochosa normalmente usada como berçário por algumas espécies de Diplodus recente classificada como Área Marinha Protegida (AMP). Variáveis ambientais como a temperatura da água do mar (SST) e do ar, período da onda e velocidade do vento explicam 53,4% da variação interanual das suas abundâncias. De 2012 a 2017 as suas abundâncias têm sofrido um decréscimo acentuado, também observado nos desembarques da pesca comercial destas espécies em lota. Esta relação mostra a importância dos trabalhos de monitorização em AMP para a gestão de recursos pesqueiros. A localização biogeográfica da costa portuguesa, na transição entre águas temperadas quentes e frias, permite observar pulsos de recrutamento de espécies de águas mais quentes interrompidos por ciclos de águas mais frias.